The Effectiveness of STEM-Based E-Modules in Enhancing Critical Thinking Skills of Elementary School Students - Wijayati, Ana Yuni; Widodo, Wahono; Istianah, Farida (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This systematic literature review examines the effectiveness of STEM-based e-modules in enhancing critical thinking skills among elementary school students. The review analyzed 24 empirical studies published between 2019 and 2025, focusing on digital learning interventions that integrate Science, Technology, Engineering, and Mathematics (STEM) approaches with electronic modules. The analysis reveals that STEM-based e-modules, particularly those incorporating Problem-Based Learning (PBL), Augmented Reality (AR), and interactive digital features, consistently demonstrate significant effectiveness in improving students' critical thinking abilities. Studies reported effect sizes ranging from 0.48 to 0.84, with most interventions showing mean score improvements of 10-20 points in critical thinking assessments. Key findings indicate that e-modules integrating virtual experiments, flipbook features, and the MIKiR model show particularly strong results in energy and renewable energy topics. However, the review identifies several limitations including small sample sizes, short intervention periods, and limited cross-regional implementation. The majority of studies utilized quasi-experimental designs with pre-post test measurements, validating the pedagogical effectiveness through expert reviews and student performance data. Despite infrastructural challenges and teacher readiness concerns, the evidence strongly supports the integration of STEM-based e-modules as an effective pedagogical tool for developing 21st-century critical thinking competencies in elementary science education. Recommendations include longitudinal studies, broader implementation across diverse contexts, and integration of emerging technologies such as artificial intelligence and metaverse platforms.